Long Run Performance of a Cold Standby Repairable System with Standby Failure subject to Maximum Operation and Repair Time - Komaldeep Kaur, R. K. Bhardwaj (Mathematical Statistician and Engineering Applications, 2023)
The failure of cold standby units in standby mode poses huge challenges to the system effectiveness. So the main goal of this contribution is to improve the system effectiveness of a two unit cold standby repairable system by taking into account the failure possibility of a unit in standby mode. The system starts functioning with the operation of one unit while another unitstays in cold standby mode. Whenever an operating unit crosses a prefix span of time (called Maximum operation time), it is sent for preventive maintenance and further if repair of the unit is not completed within a prefix span of time (called Maximum repair time) then it is replaced by a new one with some replacement time. There is provision of a server to conduct all type of repairs, maintenances, replacements and inspections. All of the random variables included in the present study follow the arbitrary distribution. The expressions for various explicit measures of system effectiveness are derived by adopting semi- Markov approach and regenerative point technique. Finally, the practical importance of the model is illustrated through numerical example and depicted in tabular form.